PENENTUAN KEBUTUHAN TENAGA KERJA MANUAL HANDLING DENGAN METODE FULL TIME EQUIVALENT (FTE) PADA LINI PRODUKSI PILUS - Prakoso, Indro; Akasa Huaida (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2024)
The fluctuation and uncertainty of the food industry market demand causes the company to maintain its productivity to be able to meet existing demand. This is also always pursued by PT XYZ as a food and beverage company. In Pilus production process, in addition to using machinery, there is still a lot of manual handling work done. Workload between jobs that cannot cause work to be completed properly, considering that humans are a factor that affects company productivity. Workload calculations are carried out using the Full Time Equivalent (FTE) method to determine the optimal number of workers. From the results of workload calculations on 42 work elements, there are 4 work elements that are overloaded and 38 other work elements are underloaded. After adjusting the workforce composition using the FTE index, it can reduce 4 workers, from 78 workers to 74 workers with a more balanced workload. The results of this study can be used as a consideration in the preparation of labor requirements and are expected to increase the productivity of Pilus production in the company.